Diversidade funcional em sistemas de montado : fluxo de nutrientes em Quercus rotundifolia Lam . Functional diversity in “ montado ” systems : nutrients fluxes in Quercus (Revista de Ciências Agrárias, 2007)
Nutrient cycling in Quercus rotundifolia Lam. systems, regarding precipitation was studied at Évora (Southern Portugal), since November of 1996 until December of 2000. The amounts of gross rainfall, throughfall (at different distances from the tree trunk) and stemflow were measured continuously and samples for chemical analysis were collected weekly. The concentration of nutrients was higher in the throughfall than in the gross rainfall, especially in the areas closer to the tree trunk. Nutrients transferred to soil, through bulk rainfall, throughfall and stemflow were quantified. The highest concentration of nutrients was observed in the stemflow water. Soil physical and chemical characteristics, underneath and outside Quercus rotundifolia crowns, were studied in areas where trees commonly are wide spaced. The amounts of the forest floor litter layer were also evaluated. Soil physical and chemical characteristics showed in general a positive effect with tree presence. Nitrogen transformation was examined under and outside the influence of the tree canopies. Nitrogen availability was higher in the soil of under crowns areas.

Influence of leaf litter type on the chemical evolution of a soil parent material (sandstone) (Biogeochemistry, 1995)
The influence of leaves of Quercus suber L. and Eucalyptus globulus Labill. and needles of Pinuspinaster Ait. on a sandstone substrate was assessed through lysimetric studies during a ten-year period at a site in Central Portugal. The decomposition rate of Q. suber leaf litter was similar to that of E. globulus and higher than that of P pinaster needle litter. The proportion of nitrogen released from the Q. suber leaf litter was higher than that lost from the other organic species. Such a release was proportional to the initial nitrogen content in the substrates. The concentrations of both NHa-N and NO3-N were much higher in leachates collected under Q. suber leaf litter than in those collected under the other organic substrates. A similar trend was found in the leachates collected under the mineral substrate influenced by the studied organic substrates. The leachate concentrations of mineral N (especially NOs-N) were higher from the mineral substrate under Q. suber leaf litter than from this organic substrate itself. The mineral substrate under leaf litter of E. globulus or needle litter of P pinaster showed an increase in exchangeable base cations and pH values, and a decrease in extractable Al. Conversely, in the substrate with Q. suber leaf litter there was only a slight increase in exchangeable base cations and pH values, and a decrease in extractable Al. These results combined with those obtained in soils underE. globulus plantations indicate that changes found in these soils are due to soil and forest m